The Little Data Book 2016 - World Bank (Washington, DC, 2016)
The Little Data Book 2016 is a pocket edition of World Development Indicators 2016. It is intended as a quick reference for users of the World Development Indicators database, book, and mobile app. The database covers more than 1,200 indicators and spans more than 50 years. The 214 country tables present the latest available data for World Bank member countries and other economies with populations of more than 30,000. The 14 summary tables cover regional and income group aggregates.